The correlation between work climate with work-related fatigue among parking ticket - Thesalonika Elisabeth Loucianna Sunkudon; Oksfriani Jufri Sumampouw; Vennetia Ryckerens Danes (Institute Of Computer Science (IOCS), 2026)
Hot work climate is a physical environmental factor that can affect both physical and mental health of workers. Continuous exposure to excessive heat without adequate control may trigger physiological responses. This study aimed to determine the correlation between hot work climate and work-related fatigue among parking ticket attendants in the Megamas Manado area. This study employed quantitative approach using an analytical survey design with cross-sectional method. The study population consisted of all 63 parking ticket attendants. Data were collected through direct measurement of heat exposure using heat stress monitor and assessment of work-related fatigue using standardized fatigue questionnaire. Statistical analysis was conducted using the Pearson correlation test. The statistical analysis revealed significant correlation between hot work climate and work-related fatigue among parking ticket attendants (p-value = 0.001). The correlation coefficient (r = 0.401) indicated moderate positive correlation, suggesting that higher heat exposure was associated with increased levels of work-related fatigue. There is significant positive correlation between hot work climate and work-related fatigue among parking ticket attendants. These findings highlight the importance of implementing effective heat control measures to reduce fatigue and improve occupational health and work performance.